Do Psychiatric Disorders or Measures of Distress Moderate Response to Postpartum Relapse Prevention Interventions?. Issue 5 (11th April 2017) - Kolko, Rachel P.; Emery, Rebecca L.; Cheng, Yu; Levine, Michele D.
Abstract: Introduction: Most women who quit smoking during pregnancy will relapse postpartum. Interventions for sustained postpartum abstinence can benefit from understanding prenatal characteristics associated with treatment response. Given that individuals with psychiatric disorders or elevated depressive symptoms have difficulty quitting smoking and that increases in depressive symptoms prenatally are common, we examined the relevance of psychiatric diagnoses, prenatal depressive symptoms, and stress to postpartum relapse prevention intervention response. Methods: Pregnant women ( N = 300) who quit smoking during pregnancy received intervention (with specialized focus on mood, weight, and stress [STARTS] or a comparison [SUPPORT]) to prevent postpartum relapse. As previously published, nearly one-third and one-quarter of women achieved biochemically-confirmed sustained abstinence at 24- and 52-weeks postpartum, with no difference in abstinence rates between the interventions. Women completed psychiatric interviews and questionnaires during pregnancy. Smoking was assessed in pregnancy, and 24- and 52-weeks postpartum. Results: Psychiatric disorders did not predict sustained abstinence or treatment response. However, treatment response was moderated by end-of-pregnancy depressive symptoms (χ 2 = 9.98, p = .002) and stress (χ 2 = 6.90, p = .01) at 24- and 52-weeks postpartum and remained significant after including covariates. Women with low distress achieved higher abstinence rates in SUPPORT than in STARTS (37% vs. 19% for depressive symptoms; 36% vs. 19% for stress), with no difference for women with high symptoms. Conclusions: Prenatal depressive symptoms and stress predicted differential treatment efficacy in women with low symptoms, not in women with high symptoms. Diagnostic history did not predict treatment differences. Future research to address prenatal distress may help tailor postpartum relapse prevention interventions. Implications: We examined prenatal history of psychiatric disorders and psychiatric distress as moderators of response to postpartum smoking relapse prevention intervention that either included or did not include added content on mood, stress, and weight concerns. For women with lower psychiatric distress, the added focus is not necessary, as these women achieved greater sustained abstinence in the less-intensive treatment. Understanding which women need which level of care to sustain abstinence can help allocate resources for all postpartum former smokers. These findings underscore the importance of perinatal symptom monitoring and promoting behavioral health more broadly in pregnant and postpartum women.